Penerapan Importance Performance Analysis untuk Peningkatan Layanan Website UMKM - aang subiyakto; Kevin Binsar Sinaga; Amelia Murniasih; Rozan Nabawi (Telkom University, 2026)
Micro, small, and medium enterprises play a strategic role in strengthening local economies, including traditional soy milk culinary enterprises in Banyumas Regency. Website utilization as a digital marketing medium has become essential due to changes in consumer behavior that rely on online information. However, the website [https://gressoy.my.id/](https://gressoy.my.id/) has never undergone a systematic evaluation, so managers lack an objective understanding of its digital service quality. This study addresses the unknown level of alignment between user importance and website performance across information, visual design, navigation, speed, security, and ordering services. This research is urgent because it provides a data driven basis for decision making to improve effective, competitive, and sustainable website management for micro enterprises. This study aims to evaluate the quality of the website using the Importance Performance Analysis method based on user perceptions and to determine priorities for digital service improvement. The results show that all attributes have high importance values, with average importance scores ranging from 4.3 to 4.7, while performance scores range from 3.3 to 3.9. The largest gaps appear in the ease of finding the ordering menu at 1.2 and website security at 1.0, indicating performance below user expectations. These findings confirm that functional aspects and trust factors play critical roles in user experience. The study recommends prioritizing digital ordering features, strengthening website security and credibility, improving visual appearance, and optimizing access speed. Periodic IPA based evaluations are also recommended to continuously enhance digital service quality and support local economic development.